2017
DOI: 10.18869/mjiri.31.5
|View full text |Cite
|
Sign up to set email alerts
|

How canola and sunflower oils affect lipid profile and anthropometric parameters of participants with dyslipidemia

Abstract: Background: Restricted intakes of saturated and trans-fatty acids and replacement with poly or monounsaturated fatty acids are emphasized in healthy diets. This study evaluates the effects of a six-month consumption of canola oil compared to sunflower oil on lipid profile and anthropometric parameters of people affected by dyslipidemia. Methods: This randomized controlled trial was conducted on 96 patients with dyslipidemia, who were randomly assigned into canola oil or the sunflower oil groups. The participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…sunflower oil for 6 weeks. Both the groups showed significant decline in LDL (Canola (Saedi et al 2017). This was another key observation of our study since obesity (increased weight, BMI and WC) is a known risk factor for CVDs.…”
Section: Change In Lipid Levelssupporting
confidence: 67%
“…sunflower oil for 6 weeks. Both the groups showed significant decline in LDL (Canola (Saedi et al 2017). This was another key observation of our study since obesity (increased weight, BMI and WC) is a known risk factor for CVDs.…”
Section: Change In Lipid Levelssupporting
confidence: 67%
“…These analyses revealed that CO ingestion does not significantly affect HC (WMD = −0.24 cm; 95% CI: −3.01, 2.54 cm, P = 0.867) (32,37,80), lean body mass (WMD = 0.01; 95% CI: −0.16, 0.19, P = 0.874) (31,33), or A:G ratio (WMD = −0.01; 95% CI: −0.03, 0.01, P = 0.271) (31,73).…”
Section: Hc Lean Body Mass and A:gmentioning
confidence: 96%
“…CO was provided to participants using different methods: using a vehicle like foods (38,47,73,74,81) or high-CO diets (31,34,39,46,(77)(78)(79)(80)(82)(83)(84)(85). The edible oils used for the control groups and periods also varied: isocaloric diets based on SFAs (79,82,83,85), olive oil (46,77,78), sunflower oil (39,80), dairy fats (34), a blend of corn and safflower oil (31), and safflower (84). Some studies used diets supplemented with a specific amount of CO for the intervention group (45, 32, 33, 35-37, 75, 76), while the control groups consumed the same diets supplemented with an equivalent amount of sunflower oil (32,36), olive oil (45,33,35,76), or fish oil (75) or simply consumed a baseline diet (37).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations